(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The aim is to reflect on how female and feminized bodies circulate a map of affects that produces an episteme epidermic. A knowledge that breaks with the assumptions of a supposedly universal knowledge that disregards in its structuring the lived body. The research has been mapping certain devices in the contemporary scene of Latin America that take on the problem. In dialogue with the scenic experiments of trans artists Lia Garcia and Renata Carvalho, and the Brazilian Theater Company ("Free Flight/Futures"), radical acts of tenderness that affirm the potency of a corporealized feminist writing-theater are investigated for both the scene and critical theory.